A gloss to the decision of the Supreme Court of November 16, 2018, I CSK 646/17 - Pieczonka, Piotr (Studia Iuridica Toruniensia, 2020)
The gloss concerns the issue of the legal consequences of the reconstruction of an independent premises and the attachment of part of the common property to it. The decision of the Supreme Court gives instructions on how to perform the act of connecting a part of the common property to an independent premises, what elements of such a legal act must include and when it is admissible and may constitute a basis for disclosing the change in the land and mortgage register.